Traditional Chinese Medicine Bone‐Setting Techniques Research Progress for the Treatment of Knee Osteoarthritis. - Fan, Qiao; Zhao, Ming-Yu; Zhang, Xiang-Dong; Chu, Tian-Yun; Kou, Zhao-Xi; Zhao, Qi; Wang, Nan; Liu, Xiao-Ying; Zhang, Jia-Hao; Wang, Qiu-Sheng; Klug, Yoel A. (BioMed Research International, 2026)
This paper systematically reviews the biological mechanisms and clinical applications of traditional Chinese medicine (TCM) manual therapy in the treatment of knee osteoarthritis (KOA), explores the scientific basis for its multipathway intervention in improving joint function, and analyzes the current research limitations. KOA is a degenerative joint disease characterized by articular cartilage degeneration, synovitis, and osteophyte formation. Its pathogenesis is closely related to mechanical stress imbalance, abnormal elevation of proinflammatory factors (e.g., IL‐1β and TNF‐α), and chondrocyte metabolic dysfunction. TCM manual therapy of KOA is to regulate the metabolism of articular cartilage and the production of inflammatory factors through the release of local soft tissue of the knee joint and supplemented by joint motion manipulation. Clinically, KOA should be treated from the perspective of syndrome differentiation, combined with modern anatomy and biomechanics, and pay attention to the circulation of the channel tendons and restore the relative stability of the human structure. In addition, manipulation combined with relevant Chinese medicine therapies such as fumigation, acupoint injection, acupuncture, and so on. can effectively relieve KOA in the elderly. However, there are still some problems in the treatment of KOA by TCM manipulation: for example, the pathogenesis of KOA is not clear, and the mechanism of action of TCM manipulation in the treatment of KOA is still under study. Whether it is the use of holistic, local, or comprehensive therapy, it is still necessary to further clarify its principle of action and better guide clinical practice.